The Effectiveness of Guided Inquiry Learning Model with Virtual Laboratory Assistance on Student Learning Outcomes on Acid-Base Materials - Hazel Salma; Emmawaty Sofya; Tasfiri Efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
This study aims to describe the effectiveness of the guided inquiry learning model with the help of a virtual laboratory on student learning outcomes on acid-base material. The population in this study were students of class XI science at SMA Negeri 14 Bandarlampung for the academic year 2021/2022, totaling 179 students. Sampling was carried out using purposive sampling technique and assigned class XI IPA 4 as the control class and XI IPA 5 as the experimental class. The research method used in this research is Quasi Experiment with Non Equivalent Control Group Design. Student learning outcomes are obtained from cognitive learning outcomes and affective learning outcomes. Based on Hake's (1998) criteria, the results showed that the average n-Gain of students' cognitive learning outcomes for the control class was 0.38 in the medium category and the experimental class was 0.67 in the medium category, and based on Arikunto's (2006) criteria the average percentage of students' affective learning outcomes for the control class is 61.13% in the high category and the experimental class is 66.81% in the high category. Based on the results of hypothesis testing, it was obtained that the average n-Gain value of cognitive learning outcomes and the average percentage of students' affective learning outcomes in the experimental class was higher than the average n-Gain value of cognitive learning outcomes and the average percentage of participants' affective learning outcomes. students in the control class, so it can be concluded that the guided inquiry learning model with the help of a virtual laboratory is effective in improving student learning outcomes on acid-base material. Keywords: Acid Base, Learning Outcomes, Guided Inquiry, Virtual Laboratory